Seasonal bird report, summer 1998, Matthew Kenne - Kenne, Matthewet al (1998)
An annotated list of birds sighted by Matthew Kenne. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1998. Epson - sheet feed